2000
DOI: 10.1002/1096-9888(200012)35:12<1434::aid-jms79>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Observation of micelle solution of decyltrimethylammonium bromide by electrospray ionization mass spectrometry

Abstract: A micelle solution of decyltrimethylammonium bromide (DTAB) was analyzed by electrospray ionization mass spectrometry. Finding an appropriate range of a capillary-skimmer potential was a prerequisite for obtaining a satisfactory spectrum. The mean molecular weight of DTAB aggregates, 10,500, was deduced from a series of mass spectra acquired at different capillary-skimmer potentials. The value was comparable with the micelle weight, previously determined by the light-scattering method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 11 publications
4
26
2
Order By: Relevance
“…However, a helicoidal or rodlike micelle with replicate structure units along one dimension cannot explain the fact that while hydrophobic effects increase the incorporation of Trp into aggregates, the enhancement decreases rapidly with increasing aggregate size ( Table 1). We note that gas-phase direct micelles have been reported for other systems, e.g., 3-[(3-cholamidopropyl)-dimethylammonio]-1-propanesulfonate (CHAPS) [52], sodium dodecylsulfate (SDS) [52], bile salt [53], and decyltrimethylammonium bromide (DTAB) [54]. Particularly, Robinson et al reported formation of gas-phase direct and reverse micelles using different ESI solutions of cetyltrimethylammonium bromide (CTAB) [51].…”
Section: Cid Of Negatively Charged Naaot Aggregatessupporting
confidence: 69%
“…However, a helicoidal or rodlike micelle with replicate structure units along one dimension cannot explain the fact that while hydrophobic effects increase the incorporation of Trp into aggregates, the enhancement decreases rapidly with increasing aggregate size ( Table 1). We note that gas-phase direct micelles have been reported for other systems, e.g., 3-[(3-cholamidopropyl)-dimethylammonio]-1-propanesulfonate (CHAPS) [52], sodium dodecylsulfate (SDS) [52], bile salt [53], and decyltrimethylammonium bromide (DTAB) [54]. Particularly, Robinson et al reported formation of gas-phase direct and reverse micelles using different ESI solutions of cetyltrimethylammonium bromide (CTAB) [51].…”
Section: Cid Of Negatively Charged Naaot Aggregatessupporting
confidence: 69%
“…In addition, the IR spectrum shows also a significant doublet at 1370 and 1380 cm −1 attributed to a polyisobutene‐amine. So these series II ions are consistent with a protonated amine structure [PA(isobutene‐amine) > PA(NH 3 )15,16]. It is suggested that the series IIa and IIb species are copolymers of N,N ‐dimethylamineisobutene and isobutene.…”
Section: Resultsmentioning
confidence: 74%
“…This was confirmed by the infrared (IR) spectrum, which showed a characteristic ether band near 1100 cm −1 . Thus the observed ions are really [M+NH 4 ] + , because the proton affinity (PA) of ethers is inferior to that of ammonia 15,16. The second series IIa and IIb are observed at high source voltages, where the ions acquire more energy in the desolvation‐acceleration region.…”
Section: Resultsmentioning
confidence: 98%
“…The spectrum is also similar to previously recorded spectra for surfactants [35][36][37] and will here be used to illustrate the spectral analysis. The intensities of bare metal ions were insignificant.…”
Section: Example Of Spectramentioning
confidence: 78%
“…The formation of such clusters, as a function of experimental variables, has been a subject of numerous studies [28 -34]. Investigations of micelle-forming systems represent a particular category of cluster investigations [35][36][37][38][39][40]. It has been found that clusters in these systems are unusually large, and it has been proposed that such clusters are formed directly from preexisting, noncovalently bonded supramolecular assemblies [35,41].…”
Section: Clusters In Esimentioning
confidence: 99%